Oxynoemacheilus isauricus, a new nemacheilid loach from Central Anatolia (Teleostei: Nemacheilidae) - Yoğurtçuoğlu, Baran; Kaya, Cüneyt; Özuluğ, Müfi̇t; Freyhof, Jörg (Zootaxa, 2021)
Oxynoemacheilus isauricus, new species, from the Lakes Beyşehir and Suğla basins in Central Anatolia is distinguished from all other species of the O. angorae group by having a very slender caudal peduncle (its depth 2.2–2.6 times in its length). The new species is further distinguished by having a short head (head length 21–24% SL), and a midlateral series of irregularly shaped blotches on the flank. Oxynoemacheilus isauricus is also distinguished by a minimum K2P sequence divergence of 7.5% and 8.0% in the mtDNA-COI barcode region from O. eregliensis and O. atili, its closest relatives.